2012
DOI: 10.1016/j.mjafi.2012.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine insemination versus fallopian tube sperm perfusion in non-tubal infertility

Abstract: . Swim up semen preparation technique was used in all cases. Insemination was performed in both groups 34e37 h after hCG administration. Standard IUI was performed using 0.5 ml of inseminate. In FSP 4 ml inseminate was used. Results: In group A (184 IUI cycles in 100 patients), 22 clinical pregnancies (presence of gestational sac with fetal cardiac activity) occurred (11.95% per cycle over four cycles). In group B, (220 cycles of FSP in 100 patients), 48 clinical pregnancies occurred (21.81% per cycle over fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…After insemination the luteal phase was supported in all participants by daily vaginal supplementation of 400 mg micronized progesterone until day of HCG test performed 14 days after insemination. The end point of the treatment cycle was either a negative pregnancy test or a positive test (serum b-HCG) confirmed by clinical evidence of pregnancy in the form of intrauterine gestational sac and fetal heart pulsation by TVS 2 weeks after positive pregnancy test [8].…”
Section: Luteal Supportmentioning
confidence: 99%
See 1 more Smart Citation
“…After insemination the luteal phase was supported in all participants by daily vaginal supplementation of 400 mg micronized progesterone until day of HCG test performed 14 days after insemination. The end point of the treatment cycle was either a negative pregnancy test or a positive test (serum b-HCG) confirmed by clinical evidence of pregnancy in the form of intrauterine gestational sac and fetal heart pulsation by TVS 2 weeks after positive pregnancy test [8].…”
Section: Luteal Supportmentioning
confidence: 99%
“…Only a median of 251 spermatozoa were recorded by flushing the tubes [4] and there was only a 49% chance of peritoneal spermatozoa to be found even when all semen characteristics were normal [5]. Many methods have been tried to improve the outcome of IUI including certain ovarian stimulation with improvement of pregnancy rate [2], perturbation 1 day before IUI [3] but Aboulghar et al [6] found no significant difference in pregnancy rate with and without hydrotubation before IUI, Fallopian tube sperm perfusion (FSP) [7,8] and intrauterine tuboperitoneal insemination (IUTPI) [9] using 4 ml and 10 ml inseminate respectively. Four milliliters of inseminate carrying spermatozoa were not sufficient to fill the uterus and Fallopian tubes and did not reach the pouch of Douglas.…”
Section: Introductionmentioning
confidence: 99%